Influência da inclinação das cúspides, tipo de retenção e envelhecimento mecânico na resistência à fratura de coroas metalocerâmicas sobre implantes - Rocha, Cibele Oliveira de Melo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this study was evaluate the influence of cusp inclination, type of retention and mechanical aging on fracture strength of implant-supported metal-ceramic (MC) single crowns. To static test, six groups were used (n=10): cemented crowns with 33° standard cusp inclination (SCI) or with 20° reduced cusp inclination (RCI), screwed crowns with screw access hole (SAH) not restored with SCI or RCI and screwed crowns with SAH restored with SCI or RCI. To test aging effect, 4 groups were used (n=20): cemented with SCI or RCI; and screw-retained with SAH not restored with SCI or RCI, in which 50% of specimens of each group were submitted to mechanical aging previously to static test. Crowns of a lower second molar were made on the analog implant external hexagon 5.0 (Biomet 3i, West Palm Beach, FL). The cycling (1.106; 125N; 10Hz) will be performed before the fracture resistance test. The static test was performed in a universal testing machine EMIC DL2000, with load application until porcelain failure. After statistical analysis it was observed that the mean fracture resistance of porcelain showed significant effect (p<0.01), to type of retention (TR) and cusp inclination (CI), respectively. To TR, screwed crowns did not show statistical differences (p>0.05), however, both two showed statistically lower values than cemented. To CI, crowns with SCI showed lower values of fracture resistance. After mechanical aging, TR and CI showed significant effect (p<0.01), with better results to cemented crowns and RCI, respectively. The factor mechanical aging did not show significant effect (p=0.659). According to these results, it was concluded that alone, type of retention and the cusp inclination showed influence on fracture resistance of MC crowns, being cemented crowns and reduced cusps mechanically more resistant against a static and cyclic load. The mechanical aging had no significant... (Complete abstract electronic access below)

O objetivo do estudo foi avaliar a influência da inclinação das cúspides, do tipo de retenção e do envelhecimento mecânico na resistência à fratura de coroas metalocerâmicas implanto-suportadas. Para o ensaio estático utilizou-se seis grupos (n=10): coroas cimentadas com cúspide de inclinação padrão (CIP) de 33º ou cúspides de inclinação reduzida (CIR) de 20°, parafusadas com o orifício de acesso ao parafuso (OAP) não-restaurado com CIP ou CIR e parafusadas com OAP restaurado com CIP ou CIR. Para o efeito do envelhecimento, 4 grupos foram utilizados (n=20): cimentadas com CIP ou CIR; e parafusadas com OAP não-restaurado com CIP ou CIR, em que 50 % das amostras de cada grupo foram cicladas mecanicamente previamente ao ensaio estático. Coroas de um segundo molar inferior foram confeccionadas sobre análogos de implante hexágono externo 5.0 (Biomet 3i, West Palm Beach, FL). O ensaio estático foi realizado aplicando-se força até a fratura da porcelana e para o efeito do envelhecimento, a ciclagem foi realizada (1 x 106; 125 N; 10Hz) antes do ensaio de resistência máxima à fratura. Após análise estatística observou-se que as médias de resistência à fratura apresentaram efeito significativo para Forma de Retenção (FR) e Inclinação de cúspide (IC) (p<0,01). Para FR apenas as coroas parafusadas não apresentaram diferenças estatísticas entre si (p>0,05), porém ambas apresentaram valores estatisticamente menores do que as cimentadas. Para IC, CIP apresentaram menores valores de resistência à fratura. Após o envelhecimento mecânico foi observado efeito significativo somente para os fatores isolados Forma de Retenção e Inclinação de cúspide (p<0,01), com melhores resultados para coroas cimentadas e CIR, respectivamente. O fator Envelhecimento Mecânico (p=0,659) não apresentou efeito significativo. Diante dos resultados, conclui-se que isoladamente... (Resumo completo, clicar acesso eletrônica abaixo)
Influence of cusp inclination, type of retention and mechanical aging on fracture strenght of the implant-supported metal-ceramics crowns
Keywords: Prótese dentária fixada por implante; Resistencia de materiais; Coroa dentária; Envelhecimento; Dental prosthesis implant-supported; Material resistance; Crowns; Aging; Materials testing